Patent Ductus Arteriosus Management and Outcomes in Japan and Canada: Comparison of Proactive and Selective Approaches - Isayama, Tetsuya; Mirea, Lucia; Mori, Rintaro; Kusuda, Satoshi; Fujimura, Masanori; Lee, Shoo K.; Shah, Prakesh S.; on behalf of the Neonatal Research Network of Japan and the Canadian Neonatal Network (American Journal of Perinatology, 2015)
Objective The aim of this study is to compare patent ductus arteriosus (PDA) management strategies and outcomes between the Neonatal Research Network of Japan (NRNJ) with proactive functional echocardiography and the Canadian Neonatal Network (CNN) with selective conventional echocardiography practice.Study Design Retrospective analyses examined very low-birth-weight infants admitted to the NRNJ or CNN in 2006 to 2008. Multivariable logistic regression analyses compared a composite outcome indicating a mortality or major morbidity (severe intraventricular hemorrhage, periventricular leukomalacia, severe retinopathy of prematurity, bronchopulmonary dysplasia, or necrotizing enterocolitis) between networks, according to PDA diagnosis and treatment, and tested the association between PDA treatment and the composite outcome within networks.Results PDA treatment (NRNJ:CNN) with conservative management (8%:16%), indomethacin only (77%:59%), ligation only (1%:13%), or indomethacin and ligation (14%:13%) varied significantly between networks. The composite outcome was lower in NRNJ versus CNN only among infants with PDA (odds ratio: 0.70; 95% confidence interval: 0.62–0.80). Surgical ligation was associated with higher composite outcome only in CNN (odds ratio: 1.79; 95% confidence interval: 1.40–2.28).Conclusion Lower composite mortality/morbidity outcome in Japan versus Canada only among infants with PDA, and association of surgical ligation with higher mortality/morbidity only in Canada, suggest differential PDA management and ligation processes contribute to outcome variation.
Keywords: patent ductus arteriosus; premature infants; echocardiography; mortality; morbidities